(NdAFTAR (B- (NI DILKU[A (B:s "(NsO^INENIE (B, (NRADU@]EE SERDCA(B"). (NfAKSIMILE TEKSTA(B/s - (NsAHIBs; (NhADI(B-(NzADE(B, (NrASUL(B.s; (Nan tADVIKSKOJ ssr OTDEL WOSTOK(B.(NI PISM(B. (NNASLEDIQ(B.s; (NoTDELENIE ISTORII an sssr s ((NmOSKWA (B:s (NnAUKA(B,s, 1965)
(NrEZ@ME NA ANGL(B. (NQZ(B.s
Keywords: (NrUKOPISI PERSIDSKIE(B, 16 (NW(B.s; (NiRAN(B- (NiSTORIQ(B, 11-13 (NWW(B. - (NiSTO^NIKI I ISTO^NIKOWEDENIE(B.s; (NpERSIDSKAQ PO\ZIQ(B, 14 (NW(B. - (NpAMQTNIKIs